Comparison of glistenings in intraocular lenses with three different materials: 12‐year follow‐up. (28th October 2011) - Rønbeck, Margrethe; Behndig, Anders; Taube, Mikaela; Koivula, Annemari; Kugelberg, Maria
Abstract. Purpose: To compare the degree of lens glistenings associated with three intraocular lenses (IOLs) of different materials and examine the relationship between the dioptric power of the optics and lens glistenings in a long‐term study. Setting: St. Erik Eye Hospital, Stockholm, Sweden. Methods: Forty‐six eyes of 46 patients underwent standard phacoemulsification and implantation with a heparin‐surface‐modified (HSM) polymethylmethacrylate (PMMA) IOL, a silicone IOL or a hydrophobic acrylic IOL. Evaluations of the patients and the glistenings were conducted 11.3–13.4 years postoperatively. The glistenings were examined using Scheimpflug imaging and subsequently analysed using an image analysis program. Results: The median follow‐up time was 12.2 years (range, 11.3–13.4). The hydrophobic acrylic IOL had significantly more lens glistenings than the silicone (p = 0.003) and the PMMA (p = 0.000) IOLs. The silicone IOL had significantly more lens glistenings than the PMMA lens (p = 0.048). The IOL power did not affect the degree of lens glistenings in the hydrophobic acrylic IOL group (p = 0.64). The other groups had too little lens glistenings to evaluate the relationship. Conclusion: In this long‐term follow‐up study, the hydrophobic acrylic IOL had a significantly higher degree of lens glistenings compared to the silicone and PMMA IOLs. The PMMA IOL had almost no lens glistenings. The IOL dioptric power was not significantly correlated with the degree of lens glistenings associated with the hydrophobic acrylic IOL.